Environmental public goods specific to agriculture - Maria Magdalena Turek Rahoveanu; Adrian Turek Rahoveanu; Petruta Turek Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Agricultural and rural development policies have had and have a great influence in developing areas over others, by intensifying the use of land and the abandonment of others, with effect on exodus of rural population to urban areas, soil erosion, the continued decline of many species and habitats, diminishing water resources, forest fires. At the same time agricultural and rural development policies have great potential in providing public goods, which the general public becomes aware of an increasing extent. Agriculture in Romania which occupies more than 60% of the land is not only responsible for the provision of raw materials and products for the food and other industries. Moreover, it has a strong influence on the environment and the countryside and therefore the environmental quality highly depends on resource management and applied management at farm level.
Keywords: 330; Public goods; the production of soybean; subsistence farms; optimizing the production of public goods